1977
DOI: 10.1007/bf00312479
|View full text |Cite
|
Sign up to set email alerts
|

A morphological and chemical study of calcification of the pineal gland

Abstract: A general scheme of analysis for the investigation of minute calcification is presented. After low temperature ashing, the samples are subjected to chemical, structural and morphological study, using atomic absorption spectrometry, infrared spectrometry, X-ray diffraction and scanning electron microscopy. Details about the calcification of the human pineal gland are given. The content of trace elements is very high, but within the limits found in other biological apatites. It is concluded that calcification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…By old age, pineal HA has a higher fluoride content than other biological apatites. Unlike pineal concentrations of magnesium, manganese, zinc and copper, which, although very high, were generally within the limits found in bone and teeth [Michotte et al, 1977].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By old age, pineal HA has a higher fluoride content than other biological apatites. Unlike pineal concentrations of magnesium, manganese, zinc and copper, which, although very high, were generally within the limits found in bone and teeth [Michotte et al, 1977].…”
Section: Discussionmentioning
confidence: 99%
“…The pineal (calcified and uncalcified) has a high trace element content (zinc, iron, manganese, magnesium, strontium and copper) in humans [Krstic, 1976;Michotte et al, 1977] and in rats Pévet, 1991, 1996]. Michotte et al [1977] suggested that, within the pineal, there are areas which are heavily loaded with calcium and which attract trace elements, even though these calcium-rich areas are not yet identifiable as concretions. Calcium is distributed throughout the pinealocytes: in the mitochondria, Golgi apparatus, cytoplasm, and nucleus [Krstic, 1976[Krstic, , 1995Welsh, 1984;Pizarro et al, 1989, Lewczuk et al, 1994.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two major forms of pineal calcifications have been observed: (i) polycrystalline complexes with dimensions of the order of hundreds of micrometers, often called mulberry-like structures or concretions [Vigh et al, 1998], and (ii) small, well defined crystals having long dimensions of the order of 10-20 mm [Lang et al, 1996]. The mulberry-like structures consist of a mineral component, hydroxyapatite, and protein and glycoprotein organic components [Krstic, 1976;Michotte et al, 1977;Ostrowski et al, 1980;Kodaka et al, 1994;Nakamura et al, 1995]. Chemical methods have been used to identify a number of elements in the pineal concretions, including Ca, P, Cu, Mn, Zn, Fe, Si, Al, Na, Mg, Cr, K, Sr, Ti, Co, and Ni [Michotte et al, 1977;Pevet, 1991, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…The mulberry-like structures consist of a mineral component, hydroxyapatite, and protein and glycoprotein organic components [Krstic, 1976;Michotte et al, 1977;Ostrowski et al, 1980;Kodaka et al, 1994;Nakamura et al, 1995]. Chemical methods have been used to identify a number of elements in the pineal concretions, including Ca, P, Cu, Mn, Zn, Fe, Si, Al, Na, Mg, Cr, K, Sr, Ti, Co, and Ni [Michotte et al, 1977;Pevet, 1991, 1996]. Various authors, using a number of different physical techniques including light microscopy, X-ray diffraction, electron probe analysis, and scanning and transmission electron microscopy, have analyzed human pineal concretions.…”
Section: Introductionmentioning
confidence: 99%